Peran Pemerintah Adat Terhadap Pemerintah Desa - Zarmaili Zarmaili (Jurnal Transformasi Administrasi, 2014)
Indonesia consists of various ethnics and cultures must have the various systems of indigenous life adopted for generations . Thus, the process of implementing the system of village government will be faced with the traditional governance system that has long been adhered to by the people in the village . This study answered how the role of government's indigenous in the governance of villages ( case study in the village of Tanjung Pauh Mudik Kerinci Jambi ). Research used qualitative descriptive approach, the data was obtained through interviews and observations of indigenous stakeholders and community leaders, as well as secondary data obtained from books or records of indigenous heritage. The result show that the process of governance in the village of Tanjung Pauh Mudik Kerinci Jambi will not run if it does not include the indigenous government. Development planning should be based on consideration of the indigenous government, as the object and regional development in the territorial government are bound by customary law and local custom values. Furthermore, the implementation of development programs by the village government should involve indigenous government in order not to deviate from customary norms. With the involvement of Indigenous Government, the implementation of rural development programs in more trusted and respected by the community. People are more obedient to the Indigenous Government, because it is a customary rule of law and governance systems that have long been attached to the people in the village and is considered clean and objective.